Gain of interaction with IRS1 by p110α helical domain mutants is crucial for their oncogenic functions - Hao, Yujun (2013)
PIK3CA, which encodes the p110α catalytic subunit of phosphatidylinositol 3-kinase α, is frequently mutated in human cancers. Most of these mutations occur at two hot-spots E545K and H1047R located in the helical domain and the kinase domain, respectively. Here, we report that p110α E545K, but not p110α H1047R, gains the ability to associate with IRS1 independent of the p85 regulatory subunit, thereby rewiring this oncogenic signaling pathway. Disruption of the IRS1-p110α E545K interaction destabilizes the p110α protein, reduces AKT phosphorylation, and slows xenograft tumor growth of a cancer cell line expressing p110α E545K. Moreover, a hydrocarbon-stapled peptide that disrupts this interaction inhibits the growth of tumors expressing p110α E545K.